Study of the obstructive sleep apnea syndrome in cerebral infarction patients - Hoang-Anh, Tien; Duong-Minh, Quy; Nguyen-Thi-Y, Nhi; Duong-Quy, Sy (Frontiers in Neurology, 2023)
Introduction: Obstructive Sleep Apnea Syndrome (OSAS) is the most common respiratory disorder during sleep. Many studies have shown an association between obstructive sleep apnea syndrome and stroke, and OSAS has not been adequately considered in Vietnam compared to the actual clinical dangers. This study aims to assess the prevalence and general characteristics of obstructive sleep apnea syndrome in patients with cerebral infarction and investigate the relationship between obstructive sleep apnea syndrome and the severity of cerebral infarction. Methods: Descriptive cross-sectional study. We identified 56 participants from August 2018 to July 2019. Subacute infarcts were identified by neuroradiologists. For each participant, vascular risk factors, medications, clinical symptoms, and neurological examination were abstracted from the medical record. Patients were taken for history, and clinical examination. The patients were divided into two groups according to their AHI (Apnea-Hypopnea Index) (< 5 and ≥ 5). Results: 56 patients were registered for the study. The mean age is 67.70 ± 11.07. The proportion of male is 53.6%. AHI has a positive correlation with neck circumference (r = 0.4), BMI (r = 0.38), the Epworth Sleepiness Scale (r = 0.61), LDL cholesterol (r = 0.38), the Modified Rankin Scale (r = 0.49), NIHSS (National Institutes of Health Stroke Scale) (r = 0.53) and an inverse correlation with SpO2 (r= 0.61). Conclusion: Obstructive sleep apnea Syndrome is a factor in the prognosis of cerebral infarction as well as cardiovascular diseases such as hypertension. Thus, understanding the risk of stroke in people with sleep apnea is necessary and working with a doctor to diagnose and treat sleep apnea is important.